Mitochondrial genome of Amphimallon solstitiale (Coleoptera: Scarabaeidae: Melolonthinae) and phylogenetic analysis. Issue 1 (2nd January 2019) - Yang, Xing-Zhuo; Zhang, Li; Feng, Run-Qiu; Zhang, Li-Jun; Luo, Fang-Zhen; Yuan, Ming-Long
Abstract: To better understand the diversity and phylogeny of Scarabaeidae, we sequenced and annotated the nearly complete mitochondrial genome (mitogenome) of Amphimallon solstitiale (Coleoptera: Scarabaeidae: Melolonthinae). This mitogenome was 13, 755 bp long and encoded 13 protein-coding genes (PCGs), 19 transfer RNA genes (tRNAs) and two ribosomal RNA unit genes. The A. solstitiale mitogenome with an A + T content of 69.45% presented a positive AT-skew (0.052) and a negative GC-skew (−0.236). Eleven PCGs started with a typical ATN codon, whereas the remaining two PCGs used CAC ( cox1 ) and GTT ( cox2 ) as the initial codon. All tRNAs had a typical secondary cloverleaf structure, except for trnS1 which lacked the dihydrouridine arm. The Bayesian phylogenetic analysis based on mitogenomic data recovered a phylogeny within Scarabaeidae as (Echirinae + (Scirtifomia + (Aphodiinae + (Melolonthinae + (Rutelinae + Cetoniinae))))).